1992
DOI: 10.1007/bf02307265
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related effects of perfluorodecanoic acid on growth, feed intake and hepatic peroxisomal β-oxidation

Abstract: The effects of the persistent peroxisome proliferator, perfluorodecanoic acid (PFDA), on growth, feed intake and the enzyme activities associated with peroxisomal beta-oxidation were studied in female Sprague Dawley rats. Rats received one of six levels of PFDA (0, 0.3, 1.0, 3.0, 10.0 or 30.0 mg/kg/injection) in four IP doses at 2-week intervals. Rats with cumulative doses of less than or equal to 12.0 mg/kg did not differ from control rats in growth or feed intake, while rats receiving cumulative doses of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…The liver is the target organ of accumulation for PFOS (Borges et al 1978;Butenhoff and Seacat 2001;Pastoor et al 1987). The concentration of PFOS in the liver was 2-3-fold greater than that found in serum.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The liver is the target organ of accumulation for PFOS (Borges et al 1978;Butenhoff and Seacat 2001;Pastoor et al 1987). The concentration of PFOS in the liver was 2-3-fold greater than that found in serum.…”
Section: Discussionmentioning
confidence: 98%
“…PFOS has been detected in the liver and blood plasma of wildlife on a global scale (Giesy and Kannan 2001). Exposure to PFOS affects the liver primarily and causes vacuolation and hypertrophy of hepatic cells (Borges et al 1978; Butenhoff and Seacat 2001;Pastoor et al 1987). PFOS also decreases body weight (BW), serum cholesterol, and triglycerides and increases liver weight (Butenhoff and Seacat 2001;Seacat et al 2002).…”
mentioning
confidence: 98%
“…The increased level of C ") : " in the livers of rats following the administration of a single high dose of PFDA has been suggested to be caused by mobilization from peripheral stores [8,9] and by the inhibition of peroxisomal β-oxidation [30]. In the present study, however, a linear correlation was confirmed between the proportion of C ") : " in microsomal lipid and the activity of ∆*desaturase in microsomes isolated from the livers of rats in five different physiological states (control, starved, starved\refed, clofibric acid-fed and PFDA-fed).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GSH and GSSG can be eliminated from liver by the action of transpeptidases and via bile secretion [13,31]. Contrast to many peroxisome proliferators, PFDA treatment lowers the flux through peroxisomal b-oxidation, even though it induced peroxisomal FAO activity as other peroxisome proliferators [32,33]. PFDA inhibits several enzymes involved in peroxisomal b-oxidation, which may decrease the rate of peroxisomal b-oxidation and H 2 0 2 production [34], but it had no effect on GSHPX [14].…”
Section: Figurementioning
confidence: 94%